Evaluation of various leguminous seeds as protein sources for milkfish juveniles. - De la Pena, Leobert
An experiment was conducted to test the nutritive value of the four leguminous plant seeds: pigeonpea (Cajanus cajan), mungo (Phaseolus radiatus), kidneybean (Phaseolus vulgaris) and soybean (Glycine max) as protein sources for milkfish juveniles, Chanos chanos (Forsskal). The legumes were added at different levels so that its protein contributed 25 of the dietary protein, while peruvian fishmeal supplied the remaining portion of a total of 40 dietary protein. A diet with all of its 40 protein contributed by fishmeal was used as a control. Substitution of 25 of the total 40 animal protein in the control diet by mungo and soybean meal did not adversely affect (P>0.05) fish growth and the efficiency of food conversion. Diets with 25 of its protein contributed by pigeonpea and kidneybean meal resulted in significantly depresses (P<0.05) growth and efficiency of feed conversion. All diets sustained a survival of more than 97 throughout the six-week experimental period. Mungo and soybean have the least cost per kg, per kg protein and per 1000 Kcal., Proximate chemical analysis of the legumes showed that soybean meal contained the highest protein and fat level at 46.8 and 14.12 respectively, and the lowest in nitrogen-free extract (NFE) at 16.11. Similar levels of protein, NFE and fat observed in pigeonpea, mungo and kidneybeanmeal. Protein ranged from 22.8 to 28.7, NFE levels were between 51.1 and 53.4 while fat levels ranged from 2.01 and 2.14. It is concluded that mungo and soybean meal contributing at least 25 of the protein can be used as replace fishmeal to reduce the costs of feed without any adverse effect on the growth, survival and efficiency of food conversion of milkfish juveniles.